The Influence of Communication and Work Environment on Employee Performance in District Government Offices - Sari, Iva Puspita; Syahputra, Erwin; Saputra, Beny Mahyudi; Dewi, Anita Sumelvia (Transpublika Publisher, 2025)
Understanding the major determinants of employee performance is essential for effective organizational management, especially in public sector organizations where the welfare of the community is directly impacted by service quality. Employee productivity and organizational effectiveness are known to be significantly influenced by communication and the work environment. The main aim of this study is to investigate the influence of Communication and Work Environment on Employee Performance at the Gurah District Office in Kediri Regency. This research focuses on variables such as communication (X1), work environment (X2), and employee performance (Y). The research methodology involves gathering data through interviews, observations, literature reviews, and surveys, using a quantitative approach. Several tests are carried out to analyse the data, including validity testing, reliability testing, classical assumption testing, multiple linear regression testing, t-testing, f-testing, and calculation of the coefficient of determination. The research in question utilised a thorough sampling method, encompassing all 36 employees at the Gurah district office based on the study's findings. Data analysis was conducted using SPSS 25.0 software with a significance level of 0.05. The results revealed that Communication (X1) had a significant effect on employee performance with a p-value of 0.032, which is below the 0.05 threshold. Similarly, Work Environment (X2) demonstrated a significant influence on employee performance with a p-value of 0.005, also below the significance level. These findings confirm that both communication and work environment significantly impact employee performance at the Gurah District Office in Kediri Regency.